Implementasi Kebijakan E-Procurement untuk Meningkatkan Transparansi, Partisipasi dan Akuntabilitas Kinerja Pelayanan Publik Di Kota Banjarmasin dan Kota Banjarbaru - , Sri Naida, S. Si ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This thesis is refer to qualitative research on case studies type, that focus on on the implementation of E-Procurement at two municipalities based on local Government Banjarmasin and Banjarbaru, South Kalimantan province as an object of research. This study has three questions reasearch and consistly to findout the three main questions. Firstly, how the implementation of eprocurement readiness and commitment of governments, businesses and people? Secondly, how e-procurement implementation performance based on principle of of transparency, participation and accountability? Thirdly, what are the constraints and challenges during implementing on e-procurement The Local Government Banjarbaru preparation on the e-procurement was started after signing the Integrity Pact in 2006. After that, had stated by the series Local Mayor Decree (Surat Keputusan Walikota or SK Walikota), an then e-procurement unit has been establisehed as a part of the institution in SKPD (Satuan Kerja Pemerintah Daerah atau Local Government Working Unit) in 2008. Meanwhile, Banjarmasin Local Government started the eprocurement in 2009, after adoption the digitalization system and of enhancing the administrative services and residence license. Also this program based on the SK Walikota. This e-procurement unit under coordination on the Public Works Department. Finally, the research has noted the Banjarmasin Local Government stated that e-procurement budgets make efficiency up to 17% in 2009-2010, whereas for the same period Banjarbaru also has the same record that to 20% efficiency. However, if viewed from the implementation of the principle of financial participation, transparency, participation and accountability measures, that has not shown that maximal performance. This study also showed, the accountability of e-procurement indicator local government Banjarmasin and local government Banjarbaru have not been going well. As the same indicator, aside as for the business/entrepreneurs is still very weak, as evidenced by not upholding the implementation of business ethics and the persistence on the procedures of e-Procurement system. Both of local government in Banjarmasin and Banjarbaru on the transparency indicators show the implementation of e-procurement has been quite good. The officials have been attempting to obtain enough information on the auction either through print or access the website LPSE. Business actors are also quite keen to follow the announcement of the tender and auction process electronically. The study also found, on participation indoicator both of them have been low, although both have activated on the participatory function through musrenbang (musyawarah rencana pembangunan or local development planning). As a result, the oversight function does not occur in e-procurement process, so this raises the question, lest to deploy the principles of accountability and transparency, both the local governments are focus on the procedural aspects and ignore the substance. Finally, this study gave the recommendations, Firstly, the necessary internal coordination of interagency in both local Government Banjarmasin and Banjarbaru, and also openness environment with the business partners. It should be a strategic effort that includes institutional arrangements, implementation procedures and also reactivation independent institution that would perform oversight functions. In addition, business ethics and morality in business, especially when following the tender, should be enforced for the city government and businesses are able to realize an integrated and efficient market.